(untitled) (Sebha University Conference Proceedings, 2024)
The research aims to identify the role of educational technology in achieving sustainable development in some faculties of Sebha University from the point of view of faculty members, and the researchers adopted the descriptive analytical approach in achieving the research objectives, and the (questionnaire tool) consisting (26) paragraphs was applied to a sample consisting of (195) faculty members who were randomly selected, divided into(47) males and (148) females, and the results of the research resulted in: The average responses of the sample members about educational technology and its role in achieving sustainable development in some faculties of Sebha University among faculty members came by (high(Also, there are no statistically significant differences about educational technology and its role in achieving the requirements of sustainable development according to the variable: (gender, years of experience; while there are statistically significant differences about educational technology and its role in achieving the requirements of sustainable development according to the variable: academic qualification in favor of (master’s), and degree in favor of (assistant lecturer).of the principles and objectives of education for also recommend that the ministry of education and higher education be notified, sustainable development in curricula and courses clearly and to define the faculty members and their students to meet the requirements f achieving sustainable development and benefiting from the experiences of other countries that preceded it in this field .